STUDI EKSPERIMENTAL PENGARUH FLY ASH DAN SERAT KELAPA PADA BETON UNTUK PERKERASAN KAKU - Suhelmidawati, Etri; Guspari, Oni; Hidayati, Rahmi; Rahmadani, Putri; Prima, Razaq (Jurnal Ilmiah Poli Rekayasa, 2025)
Concrete structures are very vulnerable to cracking due to the brittle nature of the material and strong against pressure, but weak against tension. Meanwhile, green technology and sustainable materal are popular nowadays due to global warming issues. Therefore, subtituting  material in concrete which are come from waste disposal are used in this research. Waste materials as a substitute for aggregate in concrete is currently increasing as the demand of green technology. In this research, the waste material used are fly ash and coconut fiber. Fly Ash as the replacement of cement from PLTU of Teluk Sirih and coconut fiber from Padang Pariaman will be studied. The aim of this research was to find out the effect of using Fly Ash and coconut fiber on the compressive strength and flexural strength of concrete. For the use of fiber, soaking will be carried out using NaOh which will affect the wettability angle of the fiber. The experimental method was used in this study, while the tests carried out included material testing, compressive strength test and flexural strength test. Tests carried out refer to the American Standard Testing and Materials (ASTM). Mix design were investigated based on ACI 211 4R-93 for High Strength Concrete. Based on the experimental results, the highest value of compressive strength test was attained in the 4th concrete variation with a concrete mixture of 15% Fly Ash + 1% Coconut Fiber + Sika Viscocrete with a value of 32.1 MPa and the flexural strength value as of 5.3 Mpa.